Wrist flamethrower / Muhammad Farhat Aminin Mohd Ferdaus - Mohd Ferdaus, Muhammad Farhat Aminin (2024)
This project is to present the creation of a wrist worn flamethrower. Using a modified lighter turning it into a gas cartridge and a using the concept of fluid mechanics, the gas cartridge can produce a spray of butane gas suitable for combustion. With an ignition point at the front, a small flame can be produced and shot out of the device. This project discusses about the wrist flamethrower and results that were obtained from the project made. In conclusion based on the prototype, the author discussed the advantages and points need to be considered when working on the prototype.